How does the brain affect cardiovascular health? - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
In the article the mechanisms of stress response regulation by the brain are reviewed, as well as the data from a new study in this area, which was focused on a detailed analysis of brain activity changes in people with excessive cardiovascular stress response.